Microsatellite Development And Cross Species Amplification For Characterization Of Hatchery- Bred Probarbus Jullieni - Ghiasi, Naghmeh (2009)
Probarbus jullieni is a freshwater ray-finned fish species, found in the rivers of Peninsular Malaysia, it is locally known in Malaysia as Ikan Temoleh. Its natural populations are under serious long-term decline making it to be listed by the International Union for the Conservation of Nature and Natural Resources (IUCN) Red List as ‘Endangered’ so the conservation status of P. jullieni prompted conservationists to plan some conservation programs to rescue this species. Conservation of genetic resources is an essential component of any species management program and documenting the genetic make up of both natural and farm stocks of the species is an effective strategy to guide management decision for conservation. To this aim, microsatellite markers which have a high degree of polymorphism can be useful in providing valuable information for characterizing populations. The present study had three major objectives: Detection of genetic variation in hatchery bred P. jullieni using microsatellite markers which developed for P. jullieni and also cross-amplification of microsatellite primers for closely related species and the second objective is identification and isolation of microsatellite loci in P. jullieni and the third one is identification of a sex-specific genomic DNA marker in P. jullieni by testing sex-associated markers of other fish species. Two hatchery populations of P. jullieni (Temoleh Siam and Temoleh Tarat) were used in this research. Sixteen microsatellite DNA markers comprising nine MFW and seven SYK primer pairs which were developed for the common carp Cyprinus carpio L. and Tor tambroides, respectively were tested for cross-amplification of microsatellite loci in the two populations of P. jullieni. Thirteen out of these 16 microsatellite primer pairs could detect microsatellites in P. jullieni indicating that they can be useful in studying the population structure of the fish species. In addition, six microsatellite DNA markers (Proju primers) which were developed for the seven-line barb (P. jullieni) of the Mekong River were used to determine and compare the genetic structure of these two populations of P. jullieni. These 22 primers produced 25 microsatellite loci in Temoleh Siam (ST) and 29 microsatellite loci in Tarat (T) population. The percentage of polymorphic loci was 72% in ST and 56% in T population, the number of observed allele per polymorphic locus ranged from two to six for the ST population and from two to five for the T population. The ST population showed a higher mean effective allele number (1.62) than the T population (1.35). The mean observed heterozygosity (Ho) was higher than the expected heterozygosity (He) in both populations and in the Siam population it was higher than the Tarat population. The mean FIS in both populations were negative, indicating there is no loss of variability. Eight and three loci showed significant departures from Hardy-Weinberg Equilibrium (HWE) for the ST and T populations, respectively. The analysis of molecular variance (AMOVA) based on 11 polymorphic common loci investigated, showed that 7.31% of the variations were among populations and 92.69% of the variations were within populations. The value of population pairwise FST in this study was 0.07, which indicated moderate genetic differentiation between these two populations of P. jullieni. In this study ten new microsatellite loci were isolated from P. jullieni using a Random Amplified Microsatellites (RAMs) based technique. Five out of ten were polymorphic when tested on P. jullieni’s individuals. In order to find a sex-associated marker for estimating sex-ratio in P. jullieni populations, two sex-associated primer pairs consisting of a sex specific primer set for medaka (Oryzias latipes) and a sex-associated marker for Asian arowana (Scleropages formosus) fish, were tested on the male and female samples of P. jullieni. The results showed similar banding profile between all the male and female samples. Therefore, these sex-associated DNA markers were unable to detect any differences between the males and females of P. jullieni fish.